Comparison of Renal Stones and Nephrocalcinosis in Children: Findings From Two Tertiary Centers in Saudi Arabia - Alhasan, Khalid A.; Shalaby, Mohamed A.; Albanna, Amr S.; Temsah, Mohamad-Hani; Alhayek, Zainab; Abdalla, Mohammed S.; Alotaibi, Najlaa G.; Kalakattawi, Nada M.; Zaher, Zaher Faisal; Kari, Jameela A. (Frontiers in Pediatrics, 2022)
Background: Renal stones (nephrolithiasis and urolithiasis) and nephrocalcinosis are uncommon in children; however, their incidences in pediatric populations have been increasing. Patients and Methods: This multicenter retrospective study compared the clinical presentation, etiology, and outcomes of childhood nephrolithiasis or urolithiasis with those of nephrocalcinosis. Results: The study included 144 children: 93 with renal stones and 51 with nephrocalcinosis. The mean age at presentation was 72 months and 54 months for children with renal stones and nephrocalcinosis, respectively. A history of consanguinity was found in 65% and 76% of the cases of renal stones and nephrocalcinosis, respectively. Congenital anomalies of the kidneys and urinary tract (CAKUT) were present in 28% and 9.8% of the patients with renal stones and nephrocalcinosis, respectively. The most common symptoms of renal stones were flank pain (29%), hematuria (15%), and dysuria (11%). Urinary tract infection was the primary presentation in the nephrocalcinosis group (18%), followed by failure to thrive (16%), polyuria (12%), and dehydration (12%). The majority of renal stone cases were caused by metabolic disorders, including hyperoxaluria (18%), cystinuria (18%), hypercalciuria (12%), and hyperuricosuria (2%). In contrast, the most common underlying disorders in cases of nephrocalcinosis were familial hypomagnesemia, hypercalciuria, nephrocalcinosis (35%), distal renal tubular acidosis (23%), and Bartter syndrome (6%). Clinical outcomes were significantly better in children with nephrolithiasis/urolithiasis than in those with nephrocalcinosis, who showed radiological evidence of worsening/persistent calcinosis and progressed more frequently to chronic kidney disease (stage II-IV) and end-stage kidney disease. Conclusion: The average age at presentation for children with renal stones was greater than that for those presenting with nephrocalcinosis. More than 25% of the children with renal stones were found to have CAKUT. Nephrocalcinosis was associated with worse clinical outcomes related to kidney function and disease resolution than nephrolithiasis